2021
DOI: 10.3389/fimmu.2021.674803
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-17 in Acute Pancreatitis

Abstract: Acute pancreatitis (AP) is a leading cause of death and is commonly accompanied by systemic manifestations that are generally associated with a poor prognosis. Many cytokines contribute to pancreatic tissue damage and cause systemic injury. Interleukin-17 (IL-17) is a cytokine that may play a vital role in AP. Specifically, IL-17 has important effects on the immune response and causes interactions between different inflammatory mediators in the AP-related microenvironment. In this literature review, we will di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 145 publications
1
30
0
2
Order By: Relevance
“…In addition, neutrophil extracellular trap formation pathway was activated in FMT-HTGP mice (Figure 3I), gene signatures (Padi4, Cd177, Clec7a and Mpo) that related to neutrophil extracellular trap formation were up-regulated (Figure 3H) 18 . Those pathways (IL-17, NF-kB and NOD-like receptor signaling pathways) that can drive NETs formation, were also activated in FMT-HTGP mice (Figure S3F) [19][20][21] .…”
Section: Gut Microbiota Dampens Htgp Progression By Suppressing Neutr...mentioning
confidence: 94%
“…In addition, neutrophil extracellular trap formation pathway was activated in FMT-HTGP mice (Figure 3I), gene signatures (Padi4, Cd177, Clec7a and Mpo) that related to neutrophil extracellular trap formation were up-regulated (Figure 3H) 18 . Those pathways (IL-17, NF-kB and NOD-like receptor signaling pathways) that can drive NETs formation, were also activated in FMT-HTGP mice (Figure S3F) [19][20][21] .…”
Section: Gut Microbiota Dampens Htgp Progression By Suppressing Neutr...mentioning
confidence: 94%
“…IL-10, a cytokine that combats inflammation, reduces inflammation by inhibiting cytokine production like TNF-α ( Sziksz et al, 2015 ; Palathingal Bava et al, 2022 ). Studies have confirmed that the administration of therapeutic drugs would protect SAP by attenuating the pro-inflammatory cytokine and recovering the IL-10 level, which is in line with our study ( Wang et al, 2011 ; Silva-Vaz et al, 2020 ; Li et al, 2021 ; Palathingal Bava et al, 2022 ). Further, when inhibiting autophagy, the anti-inflammatory effect of Xn was partially lost.…”
Section: Discussionsupporting
confidence: 92%
“…IL-6, as an early biomarker of severe organ failure and death, produces broad pro-inflammatory effects and leads to tissue damage ( Zhang et al, 2013 ). IL-17 affects immune responses and interacts with inflammatory mediators in SAP-related microenvironments ( Li et al, 2021 ). IL-10, a cytokine that combats inflammation, reduces inflammation by inhibiting cytokine production like TNF-α ( Sziksz et al, 2015 ; Palathingal Bava et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhong et al 32 identified USP25 as a negative regulator of interleukin (IL)17-mediated signaling and showed that Usp25 -/- mice show a greater sensitivity to IL17-dependent inflammation and autoimmunity. Because IL17 has been shown to participate in AP pathogenesis, 29 , 33 we wondered if the anti-inflammatory effects of USP25 were mediated through the modulation of the IL17 pathway. Surprisingly, when compared with the WT BMDMs, transcript levels of Il17a and downstream Ccl7 , Ccl20 , Cxcl5 , Tnf , and Cxcl1 were not increased significantly in ACS- or IL17A-exposed Usp25 -/- BMDMs ( Figure 11 A and B ).…”
Section: Resultsmentioning
confidence: 99%